2012
DOI: 10.1089/aid.2011.0373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Underlying Iron Status in Naive Antiretroviral Therapy HIV-Infected Children with Moderate Immune Suppression

Abstract: Anemia is common in HIV-infected children and iron deficiency is thought to be a common cause. This study investigates the prevalence of anemia, thalassemia, and underlying iron status in Thai and Cambodian children without advanced HIV disease to determine the necessity of routine iron supplementation. Antiretroviral (ARV)-naive HIV-infected Asian children aged 1-12 years, with CD4 15-24%, CDC A or B, and hemoglobin (Hb) ‡ 7.5 g/dl were eligible for the study. Iron studies, serum ferritin, Hb typing, and C-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Median (IQR) age was 6.8 (3.7–9.6) years, CD4% was 9 (316)% and plasma HIV-RNA was 5.2 (4.7–5.6) log 10 copies/ml at HAART initiation in those with available testing. The most common regimens were stavudine/lamivudine/nevirapine (42%) and zidovudine/lamivudine/nevirapine (25%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Median (IQR) age was 6.8 (3.7–9.6) years, CD4% was 9 (316)% and plasma HIV-RNA was 5.2 (4.7–5.6) log 10 copies/ml at HAART initiation in those with available testing. The most common regimens were stavudine/lamivudine/nevirapine (42%) and zidovudine/lamivudine/nevirapine (25%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we did not have clinical information about other possible causes of anemia (e.g., history of hemoglobinopathy, iron deficiency anemia, concurrent bone marrow-suppressive medications), nor additional clinical management or outcomes data for the patients who developed severe anemia. Kosalaraksa et al reported that mild to moderate anemia was common (around 50%) among 299 ART-naïve Thai and Cambodian children without advanced HIV (16). However, prevalence of iron deficiency anemia was low (2.7%) and the majority of cases were caused by carriage of a thalassemia trait (47%) and anemia of chronic disease (42%) (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild anemia was found to be common in ARV-naïve Thai and Cambodian children without advanced HIV. However, iron deficiency prevalence was low, with the majority of cases caused by anemia of chronic disease (Kosalaraksa et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…HIV ϩ children in Malawi were less likely to be iron deficient than HIV Ϫ children, 16 In a cohort of Thai children, the majority of HIV ϩ children with anemia were not iron deficient. 17 If HIV itself did not have pathogenic effects on the development of anemia, then the relative role of other risk factors such as nutritional deficiencies would likely be more extensive. In addition, HIV infection may also contribute to aberrant immune activation that exacerbates other etiologies of anemia.…”
Section: Multifactorial Pathogenesis Of Anemia In Hivmentioning
confidence: 99%